The islands : stories - Irving, Dionne (Catapult, 2022)
"The Islands follows the lives of Jamaican women--immigrants or the descendants of immigrants--who have relocated all over the world to escape the ghosts of colonialism. Set in the United States, Jamaica, and Europe, these international stories examine the lives of an uncertain and unsettled cast of characters. In one story, a woman and her husband impulsively leave San Francisco and move to Florida with wild dreams of American reinvention only to unearth the horrible cracks in their marriage. In another, the only Jamaican mother at a pricey prep school feels pressure to volunteer at the school's International Day. With locales ranging from 1950s London to 1960s Panama to modern-day New Jersey, author Dionne Irving reveals the intricacies of immigration and assimilation, establishing a new and unforgettable voice in Caribbean American literature. Restless, displaced, and disconnected, these characters try to ground themselves--to grow where they find themselves planted--in a world in which the tension between what's said and unsaid can bend the soul"--cover page 4.